Northwoods Nightmare - Sharpe, Jon (Sharpe, Jon. Renegade rifles., 2009)
Fargo chills in the windy wilds...Skye Fargo is guiding the well-to-do Havard family through the wilderness of British Columbia with the hope of finding their gold-prospecting son, who hasn't contacted them for months. And before the job's done, Fargo will find himself battling bitter enemies within the camp, bloodthirsty killers without, and a rich girl who likes her men hard and dirty<U+2014>like the Trailsman...